Complications of Orthodontic Treatment in Children with Dentofacial Deformities: Acute and Long-Term Outcomes - Kiriienko Юрій; Filonenko Валерій (Actual Dentistry, 2026)
Abstract. The issue of complications in the treatment of dentofacial deformities (DFDs) remains highly relevant in modern orthodontics. Identifying and addressing these complications allows orthodontists to significantly enhance the effectiveness of specialized care at all stages of comprehensive patient rehabilitation. Aim. To review the specialized scientific literature on the causes and prevention of complications during active orthodontic treatment in children with DFDs and in the long term. Materials and methods. A comprehensive search of recent domestic and international scientific literature was conducted across major databases, including PubMed, Google Scholar, and the digital repository of Bogomolets National Medical University. The analysis focused on peer-reviewed publications from recent years addressing the occurrence and prevention of short- and long-term complications during orthodontic treatment in pediatric patients with DFDs. Results and discussion. The analysis indicates that while the primary goal of orthodontic intervention is the correction of DFDs, long-term treatment stability varies significantly. Poor compliance with oral hygiene guidelines, particularly during fixed appliance therapy, leads to a wide range of complications affecting dental hard tissues, the periodontium, and the oral mucosa. To mitigate the risk of periodontal damage, clinical and radiographic-cephalometric predictors must be thoroughly evaluated during treatment planning. Mechanical tooth movement induces tissue remodeling that alters the morphology and qualitative characteristics of the periodontium. Consequently, maximizing patient satisfaction requires a balanced approach focused on achieving optimal aesthetics while minimizing both acute and long-term complications. Ultimately, orthodontic therapy must provide clear clinical benefits that outweigh any potential procedural risks. Conclusions. Treatment instability (relapse) alongside complications affecting the periodontium, dental hard tissues, and bone structures represent the most prevalent clinical challenges both during active orthodontic therapy in children with dentofacial deformities and in the long term. To prevent and mitigate these issues, a comprehensive management strategy must be implemented. This approach relies on meticulous diagnostic evaluation, patient motivation, rigorous oral hygiene protocols, elimination of the primary etiological factors of deformities, control of tooth movement utilizing light forces, and careful consideration of individual anatomofunctional characteristics.